Drivers of long-term carbon dynamics in cropland: A bio-political history (France, 1852–2014). Issue 93 (March 2019) - Le Noë, Julia; Billen, Gilles; Mary, Bruno; Garnier, Josette
Graphical abstract: Highlights: Net primary production and carbon inputs govern carbon storage in cropland. Carbon storage in cropland depends on the trajectory of regional agro-food system. Three historical periods of carbon storage in cropland were identified. Currently carbon storage does not offset the emissions of the agricultural sector. Mitigation of C emissions requires a reconfiguration of agro-food system metabolism. Abstract: Following the COP 21, it has been widely recognized that agricultural soils may contribute toward mitigating or enhancing climate change depending on their behavior as a sink or a source of carbon (C) to the atmosphere. Here, we studied the case of soil organic carbon (SOC) stocks in French cropland at the regional scale from 1852 to 2014 by coupling the GRAFS approach (Generalized Representation of Agro-Food System) with the AMG model (after its authors names: Andriulo, Mary, Guérif). Our results emphasize the role of crop net primary production (NPP) as the main driver of changes in SOC stocks through the input of crop residues. Three distinct phases of NPP were identified: (1) from 1852 to 1950, a slow rise in NPP occurred, which induced a moderate increase of cropland SOC pools (1–2‰ yr −1 ); (2) from 1950 to 1980, NPP increased considerably, resulting in a much higher rate of SOC accumulation (2–4‰ yr −1 ); (3) from 1980 to 2014, divergent trajectories were followed according to regions with either a slowdown in NPP growth with moderate increase in SOC stocks (0–2‰ yr −1 ), or a reversed trend toward declining NPP induced by a reduction of fodder production, replaced by imported feed which led to negative change of cropland SOC stocks. We highlight that these evolutions of carbon dynamics in cropland were closely linked to changes in the French social political context, from the second Empire to the Cold War and the advent of a neo-liberal era. As a whole, for France, we found a rate of C sequestration in the top 30 cm of cropland soils of about 1.7 Mt C yr −1 for the last two decades, less than one fifth of the current fossil-fuel-based CO2 emission rate of the French agricultural sector which exceeds 8 Mt C yr −1 . Our study showed that in developed countries like France, where a sharp increase in cropland SOC stocks occurred owing to the modernization of agriculture, this should be considered as a "fossil-fuel-powered carbon sink", which does only partly compensate for the direct emissions through mechanization and fertilizer production that induced it.